Work stress in aircraft maintenance technicians: The role of work-life balance - Cucunda Resi Anggarini; Indrayanti Indrayanti (HUMANITAS: Indonesian Psychological Journal, 2021)
Work stress is a widespread issue among various kinds of employees because of its negative impact. This study aimed to determine the role of work-life balance toward work stress experienced by aircraft maintenance technicians. A total of ninety-two aircraft maintenance technicians participated in this quantitative approach using scales as the research instrument. The data were collected and then analyzed using multiple linear regression methods. The results showed that three dimensions of work-life balance, namely WIPL, PLIW, and WPLE, have a significant simultaneous role on work stress with an effective contribution of 56.5%. Partially, WIPL and PLIW significantly have a positive role on work stress with a contribution of 40.7% and 12.19%, whereas WPLE does not have a significant role on work stress. This study implies that a low level of WIPL and PLIW will reduce work stress levels in aircraft maintenance technicians and vice versa. Therefore, organizations can support aircraft maintenance technicians in managing work-life balance to maintain work stress levels.